New developments on Waqf laws in Malaysia: are they comprehensive? - Mohamad, Nor Asiah; Syed Abdul Kader, Sharifah Zubaidah (Universitas Muhammadiyah Yogyakarta, 2017)
Five (5) states in Malaysia have introduced their own waqf laws. The other five (5) states are working on new laws and the remaining states maintain waqf matters in the general statutes on administration of Islamic law. The new developments which took place in the 5 states are expected and most awaited after voluminous researches reveal that the legal framework has contributed to the slow development of waqf in Malaysia. Using the doctrinal approach and comparative analysis method, this study reviews the latest developments in the waqf enactments of Selangor, Perak and Terengganu and discusses how the changes in the laws have helped to improve the slow and restricted jurisdiction (legal framework?) dealing with waqf. The findings show that the new Enactments have addressed most of the observations from the previous literatures especially with regards to challenges in waqf development. Observations also relate to the fast development of waqf which moves in tandem with various other aspects of the economy and finance. Waqf is now recognised as the third economic sector in several jurisdictions. In addition, the need to employ Islamic finance products as vehicles for waqf development has also been recognised by the stakeholders. Although new laws are welcomed, the awareness on the emerging new needs is vital.